(x^2−3x)^2+3(x^2−3x)+2=0
Question
Check here step-by-step solution of '(x^2−3x)^2+3(x^2−3x)+2=0' question at Instasolv!
Fullscreen

( left(x^{2}-3 xright)^{2}+3left(x^{2}-3 xright)+2=0 )

JEE/Engineering Exams
Maths
Solution
94
Rating
4.0 (1 ratings)
(x^2−3x)^2+3(x^2−3x)+2=0
Fullscreen

( left(x^{2}-3 xright)^{2}+3left(x^{2}-3 xright)+2=0 )
( left(x^{2}-3 x+1right)left(x^{2}-3 x+2right)=0 )
( x^{2}-3 x+1=0 quad ) or ( quad x-3 x+2=0 )
( x=3 pm sqrt{9-4} quad ) or ( quad(x-1)(x-2)=0 )
( Rightarrow x=frac{3 pm sqrt{5}}{2} quad ) or ( quad x=1,2 )

Quick and Stepwise Solutions Just click and Send Download App OVER 20 LAKH QUESTIONS ANSWERED Download App for Free